Small-Molecule Modulators of Sigma1 and Sigma2/TMEM97 in the Context of Cancer: Foundational Concepts and Emerging Themes - Oyer, Halley M.; Sanders, Christina M.; Kim, Felix J. (Frontiers in Pharmacology, 2019)
There are two known subtypes of the so-called sigma receptors, Sigma1 and Sigma2. Sigma1 (encoded by the SIGMAR1 gene and also known as sigma-1 receptor, S1R) is a unique pharmacologically regulated integral membrane chaperone or scaffolding protein that allosterically modulates the activity of its associated proteins. There are two known subtypes of the so-called Sigma receptors, Sigma1 and Sigma2. Sigma1 (encoded by the SIGMAR1 gene and also known as Sigma-1 receptor, S1R) is a unique pharmacologically regulated integral membrane chaperone or scaffolding protein that allosterically modulates the activity of its associated proteins. Sigma2, recently identified as transmembrane protein 97 (TMEM97), is an integral membrane protein implicated in cellular cholesterol homeostasis. A number of publications over the past two decades have suggested a role for both Sigma proteins in tumor biology. Although there is currently no clinically used anti-cancer drug that targets Sigma1 or Sigma2/TMEM97, a growing body of evidence supports the potential of small-molecule compounds with affinity for these proteins, putative Sigma ligands, as therapeutic agents to treat cancer. In preclinical models, these compounds have been reported to inhibit cancer cell proliferation, survival, adhesion, and migration; furthermore, they have been demonstrated to suppress tumor growth, to alleviate cancer-associated pain, and to exert immunomodulatory properties. Here, we will address the known knowns and the known unknowns of Sigma1 and Sigma2/TMEM97 ligand actions in the context of cancer. This review will highlight key discoveries and published evidence in support of a role for Sigma proteins in cancer and will discuss several fundamental questions regarding the physiological roles of Sigma proteins in cancer and Sigma ligand mechanism of action.